2014
DOI: 10.2147/ppa.s72408
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the level of satisfaction of patients utilizing first-level health facilities as a function of health system performance rating in the province of Elazig, Turkey

Abstract: PurposeThis study was conducted to determine the level of satisfaction of patients utilizing first-level health care facilities as a function of health system performance rating in Elazig province of Turkey.MethodsThe study was conducted between December 2013 and March 2014 at the family health centers in the Elazig province center. For collecting the data in the cross-sectional study conducted with 1,290 patients, personal data form for patients and the Turkish version of European Patients Evaluate General/Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…This finding is consistent with the study conducted in West Gojjam Zone [28]. In studies from clinical care setup and with a paid service, monthly income was inversely associated with satisfaction [29] or else did not show any association with satisfaction to the service [30][31][32]. Women from a higher family income might be more educated, autonomous in household decisions and health care choices and would also have better alternatives in accessing the curative services provided in other higher-level institutions.…”
Section: Plos Onesupporting
confidence: 90%
“…This finding is consistent with the study conducted in West Gojjam Zone [28]. In studies from clinical care setup and with a paid service, monthly income was inversely associated with satisfaction [29] or else did not show any association with satisfaction to the service [30][31][32]. Women from a higher family income might be more educated, autonomous in household decisions and health care choices and would also have better alternatives in accessing the curative services provided in other higher-level institutions.…”
Section: Plos Onesupporting
confidence: 90%
“…92 In Turkey, earlier small area studies found that the expansion of the FMP was associated with significant improvements in consumer satisfaction. 93,94 More recently, one study that used nationwide data also concluded that the expansion of the FMP was associated with significant improvements in consumer satisfaction with clinical behaviors of FMP professionals, a composite measure that tracked 18 different aspects of care (e.g., listening to patients), as well as the process of care (e.g., obtaining an appointment at a time that suits the patient). 95 However, these studies fell short of isolating the potential role that the organizational PHC reforms may have played in the observed improvements in client satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Bulut and Oguzoncul (2014) use the same data to examine differences in satisfaction rates with the Family Medicine Model between socioeconomic groups in a single province. They found that on average males, those who had completed secondary school education, farmers, and patients with incomes between 1,001–2,500 Turkish Lira reported significantly higher rates of satisfaction as compared to other respondents [28]. Through a cross-sectional study conducted between October 2011 and January 2012, Jadoo et al (2014) observed that more than two-thirds of respondents believed that the Health Transformation Programme had a positive impact on Turkey’s health system [29].…”
Section: Discussionmentioning
confidence: 99%